Appointment of Village Apparatus From A Good Governance Perspective in Wori District, North Minahasa Regency - Mayuntu, Oktavianus Jus; Mandagi, Marthinus; Tumbel, Goinpeace H. (Technium Social Sciences Journal, 2024)
This research aims to 1) To see the process of appointing village officials in accordance with the principles of good governance; 2) To find out and analyze what are the inhibiting and supporting factors for Village Heads in Wori District in Recruiting Village Officials in Wori District, North Minahasa Regency; 3) To find out and analyze how the Village Head in Wori District considers improving the professionalism of village officials from a good governance perspective. This research uses qualitative research methods with the focus of the research being the process of appointing village officials in Darunu Village, Wori District, North Minahasa Regency, taking into account the principles of good governance. The results of the research show that both the selection and appointment processes have met the requirements for good governance, seen in a transparent and accountable manner, where information on selection and recommendations up to appointment follows the principles of transparency. Then, in terms of accountability, all village officials must have accountability requirements in terms of completeness of documents, and education level, then they must go through the stages of screening and recommendation from the Head of the District, and then the Village Head is appointed. The results of the screening, recommendations from the Head of the District, and the appointment of Village Apparatus are carried out openly and then obey the law, where the consideration of the Head of Darunu Village can still be said to be sufficient because there are authorities that must be taken into account, such as the authority of the Head of the District and must be based on a clear legal umbrella and its application in the community still receives many complaints.